Internationalization of Healthcare Companies to Developing Countries - Wiman, Stella (My University, 2024)
Healthcare markets around the world are quickly evolving and expanding. Internationalizing into developing countries is more crucial than ever, as these markets increasingly play a key role in the strategic objectives of healthcare companies. This thesis investigates the advantages of internationalization from the perspectives of both the company and the host countries, alongside with the potential threats and key considerations for expanding into developing countries. This thesis assesses the influence of internationalization on local sustainable development and explores the strategic use of CSR initiatives to enhance corporate brand image. Furthermore, this thesis proposes a reverse innovation framework, offering benefits both the company and the host countries. It also presents real-life examples of successful reverse innovation. In addition to analyzing benefits and opportunities internationalization is able to bring, this thesis aims to analyze the landscape of developing countries through a PESTEL analysis, focusing on potential external threats that healthcare companies should acknowledge when considering internationalization. Additionally, the analysis of potential threats analyzes the risk of losing stakeholders’ trust, illustrated through a real-life case. The goal of this thesis is to give valuable insights and evaluations that will guide healthcare companies in shaping their future strategies.

Terveydenhuollon markkinat kehittyvät ja laajenevat nopeasti. Kansainvälistyminen kehittyviin maihin on tärkeämpää kuin koskaan, sillä nämä markkinat ovat yhä keskeisimpiä terveydenhuollon yritysten strategisille tavoitteille. Tässä kandidaatintutkielmassa tutkitaan kansainvälistymisen etuja yrityksen ja kohdemaan näkökulmasta, sekä analysoidaan mahdollisia uhkia ja ilmiöön vaikuttavia ydintekijöitä. Tutkielma arvioi kansainvälistymisen vaikutuksia kohdemaan kestävän kehityksen edistämisen näkökulmasta, sekä tutkii yritysvastuun (CSR) ja sitä edistävien toimien vaikutusta strategiana parantaa yrityksen brändi-imagoa. Tutkielmassa tutkitaan myös teorian ”reverse innovation” vaikutusta sekä yritykselle että kohdemaalle, havainnollistaen teorian strategista hyötyä todellisen esimerkin avulla. Kansainvälistymisen hyötyjen ja mahdollisuuksien tutkimisen lisäksi tutkielma analysoi kehittyvien maiden liiketoimintaympäristöä PESTEL-analyysin avulla, tarjoten tietoa ulkoisista uhista, jotka yrityksen tulisi ottaa huomioon kansainvälistyessään. Ulkoisten uhkien lisäksi tutkielma käsittelee myös riskiä sidosryhmien luottamuksen menettämisestä, analysoiden ilmiötä esimerkin avulla. Tutkielman tavoitteena on antaa terveydenhuollon yrityksille arvokkaita näkökulmia kansainvälistymiseen kehittyviin maihin, antaen työkaluja tulevaisuuden strategiseen suunnitteluun.
Keywords: internationalization, health care, developing countries, CSR, PESTEL, market entry, brand image, sustainable development, reverse innovation, kansainvälistyminen, terveydenhuolto, kehittyvät maat, kestävä kehitys, yritysvastuu, brändi-imago